2012
DOI: 10.1155/2012/908547
|View full text |Cite
|
Sign up to set email alerts
|

Experience of Initial Symptoms of Breast Cancer and Triggers for Action in Ethiopia

Abstract: Objective. This study assessed the initial experiences, symptoms, and actions of patients in Ethiopia ultimately determined to have breast cancer. Methods. 69 participants in a comprehensive breast cancer treatment program at the main national cancer hospital in Ethiopia were interviewed using mixed qualitative and quantitative approaches. Participants' narratives of their initial cancer experience were coded and analyzed for themes around their symptoms, time to seeking advice, triggers for action, and contex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
77
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(82 citation statements)
references
References 16 publications
4
77
1
Order By: Relevance
“…Consistent with other studies, while women who attributed the symptoms to minor conditions, ignored symptoms without any emotional response (de Nooijer et al, 2001;Dye et al, 2012), nearly all women who perceive the seriousness of the various forms of fear and concern (Adam and Soutar, 2003;Lu et al, 2010;O'Mahony et al, 2011). In this study, not only understanding the seriousness of the symptoms caused negative psychological reactions, but also in some cases, fear of cancer led to hesitation in accepting the seriousness of the symptoms.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Consistent with other studies, while women who attributed the symptoms to minor conditions, ignored symptoms without any emotional response (de Nooijer et al, 2001;Dye et al, 2012), nearly all women who perceive the seriousness of the various forms of fear and concern (Adam and Soutar, 2003;Lu et al, 2010;O'Mahony et al, 2011). In this study, not only understanding the seriousness of the symptoms caused negative psychological reactions, but also in some cases, fear of cancer led to hesitation in accepting the seriousness of the symptoms.…”
Section: Discussionsupporting
confidence: 87%
“…The absence of pain in patients who consider painful lump to be a symptom of cancer creates false confidence (Burgess et al, 2001). Several studies have shown that painless lump was attributed to not being serious and was more common in delayed presentations (Lam et al, 2009;Taib et al, 2011;Dye et al, 2012). Dye et al (2012) reported that changes in nature of symptoms (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies reported that self-awareness is more effective than BSE [32] and it appears that BSE training could provide an opportunity to increase women's knowledge about breast cancer in developing countries [33][34].…”
Section: Discussionmentioning
confidence: 99%